Impact of energy innovations on the Ukraine’s economy: Strategic direction and managerial practices - Trofymenko Olena; Ilyash Olha; Voitko Serhii; Dluhopolska Tetiana; Kozlovskyi Serhii; Hrynkevych Svitlana (ECONOMICS, 2022)
Diversification of energy sources and innovative development of the energy sector are one of the main directions for ensuring sustainable development and decarbonization of the economy. The aim of the article is to identify connections and interactions between the parameters of energy innovation development and economic growth. Factor analysis was used for this purpose. The results and conclusions determine the most influential factors among the 5 components identified in accordance with the functional areas of innovative development of the national economy in energetics. The analysis allowed to identify the main trends in the development of factors, which allowed to identify positive and negative changes. The regularities of the influence of certain factors on energy innovations have been determined, which has allowed to provide recommendations for their further development and regulation